Pension Reform and Labor Supply: Flexibility vs. Prescription - Erik Hernæs; Simen Markussen; John Piggott; Knut Røed (Institute for the Study of Labor (IZA), 2015)
We exploit a comprehensive restructuring of the early retirement system in Norway in 2011 to examine labor supply responses to alternative pension reform strategies relying on improved work incentives (flexibility) or increased access ages (prescription), respectively. We find that increasing the returns to work is a powerful policy tool: The removal of the earnings test at age 63 led to an immediate increase in average annual labor earnings among the affected mature workers by around 14,700 (NOK 90,000). The implied uncompensated labor earnings elasticity (the percentage change in average gross earnings relative to the percentage change in average work-incentives) is around 0.25.
Keywords: H55; J22; J26; 330; early retirement; labor supply; pension reform; program evaluation